The Effectiveness of Digital Story Telling in EFL Classroom - Richo Hermawan Budianto; Juang Kurniawan Syahruzah (Journal of English Language Teaching and English Linguistics, 2022)
The research aims to find out the effectiveness of Digital Story Telling media in listening class students at University of PGRI Yogyakarta. This research was experimental research which used quasi experimental method. Therefore, the data were collected by observation, interview, test, and questionnaire. Samples of this research were 28 students of 10 male and 18 female in the second semester English department students. The samples were divided into two groups, there were experiment group and control group. Both of groups were given pretest before treatment and posttest after treatment. Students in experiment group got treatment to study English listening by Digital Story Telling. The result of the research shows that Digital Story Telling is effective to improve listening skill. Result of the hypothesis measured from the post-test of the experiment class. The result shows the value of significance t-test is 0.000 which is lower than 0.05. It means that Ha is accepted and H0 is rejected. Mean of control group in pre-test is 34.28, thus in experiment group is 37.85. Mean of control group in post-test is 39.28, while in experiment group 47.14. It concludes that Digital Story Telling as media is effective to improve student in learning listening at second-semester student in English Language Education Study Program at the University of PGRI Yogyakarta.